Is It Necessary to Do Temporal Bone Computed Tomography of the Internal Auditory Canal in Tinnitus with Normal Hearing? - Tolgar Lutfi Kumral; Guven Yıldırım; Huseyin Baki Yılmaz; Seckin Ulusoy; Guler Berkiten; Suzan Deniz Onol; Yusuf Ozturkçu; Yavuz Uyar (The Scientific World Journal)
Objective. To investigate the compression of the vestibulocochlear nerve in the etiology of the tinnitus in the normal hearing ears with temporal bone computed tomography scans. Methods. A prospective nonrandomized study of 30 bilateral tinnitus and 30 normal hearing patients enrolled in this study. Results. A total of 60 patients (ages ranged from 16 to 87) were included. The tinnitus group comprised 11 males and 19 females (mean age 49,50 ± 12,008) and the control group comprised 6 males and 24 females (mean age 39,47 ± 12,544). Regarding the right and left internal acoustic canals measurements (inlet, midcanal, and outlet canal lengths), there were no significant differences between the measurements of the control and tinnitus groups (P>0.005). There was no narrowness in the internal acoustic canal of the tinnitus group compared with the control group. High-frequency audiometric measurements of the right and left ears tinnitus group at 8000, 9000, 10000, 11200, 12500, 14000, 16000, and 18000 Hz frequencies were significantly lower than the control group thresholds (P<0.05). There was high-frequency hearing loss in the tinnitus group. Conclusion. There were no anatomical differences in the etiology of tinnitus rather than physiological degeneration in the nerves.